Pengembangan bahan ajar matematika bermuatan keislaman pada materi pecahan - Mulhamah, Mulhamah (JP3M: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN MATEMATIKA, 2018)
This research aims to development learning devices with contain islamic problems (inheritance law) in mathematics learning in fractions. This research develops product of hand outs and student worksheet using the design of  ADDIE models (Analysis, Design, Development, Implementation, and Evaluation). Implementation development product using an assessment instrument in terms of validity, practicality, and effectiveness. This research produces hand out and worksheet that are valid, practical, and effective.